IMMU-37. DISRUPTION OF PD-L1 BY ENHANCED TWO-SGRNAS CRISPR/CAS9 IN TREATMENT OF GLIOBLASTOMA. (12th November 2021) - Fierro, Javier; Perez, joshua; Aguilar, Rocio; Dipasquale, Jake; Tran, An; Factoriza, Chris; Dou, Huanyu
Abstract: Anti-glioblastoma multiform (GBM) immunotherapy poses a great challenge due to immunosuppressive brain tumor environments and the blood brain barrier (BBB). Programmed death ligand 1 (PD-L1) plays a key role in GBM immunosuppression, vitality, proliferation, and migration. Targeting PD-L1 for immunotherapy is a promising new avenue for treating GBM. CRISPR/Cas9 gene editing can be used to knockout both membrane and cytoplasmic PD-L1, leading to an enhanced immunotherapeutic strategy. We identified two sgRNA sequences located on PD-L1 exon 3. The first sgRNA recognized the forward strand of human PD-L1 near the beginning of exon 3 and cuts at approximately base pair 82 (g82). The second sgRNA recognized the reverse strand of exon 3 and cuts at base pair 165 (g165). Two sgRNAs, g82 and g165, created an 83bp deletion in PD-L1 genomic sequence. Two sgRNAs combination with a homology-directed repair template (HDR) was designed to enhance PD-L1 knockout specificity and efficiency. Both g82 and g165 were cloned into one CRISPR/Cas9 plasmid, and was co-transfected with HDR. GFP tagged CRISPR/Cas9 plasmid containing of g82 and g165 (Cas9-g82/165) was loaded into Rhodamine labeled nanoparticles (Cas9-g82/165-NPs) and then treated to GBM U87 cells. The enhanced intracellular uptake and transfection of Cas9-g82/165-NPs were detected by a fluorescence microscopy. T7E1, qRT-PCR and western blot analysis determined that the dual sgRNA CRISPR/Ca9 system knocked out both endogenous (80%) and exogenous (64%) PD-L1 in U87 cells and PD-L1 overexpression U87 cells, respectively. Deletion of PD-L1 reduced U87 migration and proliferation, while PD-L1 overexpression promoted tumor growth and tumor-associated macrophage polarization. Together, deletion of both membrane and cytoplasmic PD-L1 altered the PD-L1-associated immunosuppressive environment and prevented tumor progression and migration. Thus, two-sgRNAs CRISPR/Cas9 gene-editing system is a promising avenue for anti-GBM immunotherapy.